1996
DOI: 10.1161/01.cir.93.11.1963
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Brain Natriuretic Peptide as an Indicator of Left Ventricular Systolic Function and Long-term Survival After Acute Myocardial Infarction

Abstract: These results suggest that plasma BNP determination provides important, independent prognostic information after AMI. Although plasma ANP appears to be a better predictor of left ventricular dysfunction, plasma BNP may have greater potential to complement standard prognostic indicators used in risk stratification after AMI because of its strong, independent association with long-term survival, enhanced in vitro stability, and simplicity of analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
390
7
12

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 660 publications
(440 citation statements)
references
References 43 publications
31
390
7
12
Order By: Relevance
“…Our results expand knowledge of earlier findings of enhanced risk prediction using natriuretic peptides in patients with a recent ACS3, 10, 11, 12 to also include patients with a recent ACS and type 2 diabetes mellitus. This prevalent population has only marginally been studied in this context 37, 38, 39, 40.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results expand knowledge of earlier findings of enhanced risk prediction using natriuretic peptides in patients with a recent ACS3, 10, 11, 12 to also include patients with a recent ACS and type 2 diabetes mellitus. This prevalent population has only marginally been studied in this context 37, 38, 39, 40.…”
Section: Discussionsupporting
confidence: 83%
“…However, as the incidences of outcomes differ between patients with HF8 and patients with a recent ACS9 in a stable phase, it is less established how natriuretic peptides are associated with cardiovascular outcomes, especially subsequent MI and stroke, in the latter population 3, 10, 11, 12, 13, 14. Concentrations of natriuretic peptides may be affected by both asymptomatic myocardial ischemia15, 16 and atrial fibrillation,17, 18 which could make BNP and NT‐proBNP relevant as predictors of MI and stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated a similar pattern of risk for patients with elevated NT-proBNP (5,6,(13)(14)(15)(16)(17)(18). Our study extends these prior findings by demonstrating that, at baseline, 24 h and 72 h, NT-proBNP predicts adverse events independent Other studies have demonstrated that BNP predicts adverse events, particularly sudden cardiac death, in both the postmyocardial infarction (19) and heart failure populations (20).…”
Section: Prognosissupporting
confidence: 84%
“…The power, sensitivity and specificity of the natriuretic peptides as predictors of mortality needs to be defined more clearly. Furthermore, the comparative predictability of the ventricular hormone, BNP, and its amino-terminal peptides [28,31] requires clarification.…”
mentioning
confidence: 99%